Digital Trends of Criminology and Criminal Justice of the 21st Century - M. R. Asli (Journal of Digital Technologies and Law, 2023)
Objective: to define the key trends in the development of criminology and criminal justice under significant broadening of digitalization and using modern technologies.Methods: the priority of analytical method combined with descriptive method provided an optimal set of tools for searching and revealing the main digital trends in the development of criminology and criminal justice in the 21st century.Results: the growing dependence was revealed between criminal-legal science and digital technologies, which leads to the change in essence and types of contemporary criminality, models of criminals’ behavior, methods and mechanism of crime control and prevention in the light of requirements of criminal policy and justice. The dual role of the global digitalization trend is highlighted, the achievements of which are used both by the agencies of criminal justice system (in particular, for crime control, management and prevention) and criminals when implementing their criminal intents. It was determined that the essential transformation of criminology and criminal justice is largely caused by a dramatic development of digitalization in the 21st century, as well as by the modern technologies created on its basis, which appear to be more effective than the standard methods of traditional criminology, including quantitative and qualitative estimations, observation, interviews, polls, etc.Scientiﬁc novelty: new spheres of criminal-legal knowledge are introduced, as well as the corresponding disciplines formed exclusively under the influence of digitalization, such as cyber criminology and cyber victimology; algorithmic (computational) criminology, based on actuarial justice and the theory of risks, is highlighted as the most recent trend in criminological science.Practical signiﬁcance: the account of trends and positive experience gained in the sphere of digitalization determines the successful solution of the tasks associated with crime counteraction, transformation of approaches to the content, goals and methodology of applied criminology and criminal justice. The global megatrend of digitalization essentially changes the appearance of the criminal-legal science, sets the new theoretical and applied directions of its development. Timely upgrade and adaptation of knowledge, skills and capabilities in compliance with the achievements of digitalization will allow criminology and criminal justice to correspond to the tasks of the new millennium.